The system of inheritance distribution in South Sulawesi - Abdul Mutakabbir; Hastuti Hastuti; Mikdar Rusdi (State Islamic University of Salatiga, 2023)
This article describes the inheritance distribution system of the people of South Sulawesi. This research uses interviews with several community and religious leaders who understand inheritance law. The research sites are Makassar, Pinrang, Palopo and Bone. The theory used is maṣlaḥah mursalah, which analyzes data about the inheritance system, starting from the process of inheritance division and the number of heirs' shares, as well as the interplay between customary law and Islam in the inheritance distribution system in South Sulawesi. Without removing the core of inheritance law, the South Sulawesi people's way of distributing inheritance makes use of the customary law known as ade' in the pangadereng system. There are three types of distribution, depending on whether the family is still together, whether one parent has deceased, or whether both parents have deceased. The nominal distribution varies, sometimes it is equal and other times it is based on fairness, which means that heirs who have invested a lot of money, such as those who go to high school and live well, give up their rights to relatives who are less established or who remain with the parents in the village. According to the benefit principle, men typically receive a plot of land because they have the energy to cultivate it, while women typically receive a house. This study shows how the customary division system emphasizes the common good in order to fulfill a number of maqāṣid al-shari’ah ideals, including the protection of property, honor, and life (soul).